The role of CD40/CD40L pathway in biological activity of blood platelets: part II - Saluk-Juszczak, Joanna; Królewska, Karolina (Menopause Review/Przegląd Menopauzalny, 2010)
The main function of blood platelets is their haemostatic role, but recent evidence shows that processes of platelet activation may be sometimes a critical link between haemostasis and development of inflammation. The discovery of expression of CD40 and its ligand – CD40L on platelet surface revealed the participation of these cells in immune responses and inflammation. In many pathological processes related to cardiovascular disorders, e.g. changes connected with menopause, enhanced platelet activation is observed in atherosclerosis, diabetes and cancer, in which proinflammatory and prothrombotic CD40/CD40L pathway is involved. Signals that drive inflammatory events and are transmitted through CD40/CD40L pathway cause the inflammatory cell interactions leading to induction of innate immune response. This signal transduction is associated with the release of adhesion molecules, chemokines, cytokines, tissue factors, reactive oxygen species, growth factors and other proinflammatory mediators from activated cells. Hyperactivity of platelets associated with signal transduction by CD40/CD40L pathway is observed in many pathogenic processes, including thrombosis, diabetes, inflammation and cancers. The inhibition of CD40/CD40L pathway may provide alternative treatment for various diseases in the future.